National survey of B1 and B2 reporting of breast needle core biopsies. Issue 3 (9th October 2015) - Deb, Rahul; Jenkins, Jacquie A; Rowlands, David; Ellis, Ian O; Lee, Andrew HS
Abstract : Aim: This survey investigated the variation in the use of the breast core biopsy categories B1 normal and B2 benign. Method: A survey with case scenarios was circulated to 701 breast pathologists in the UK. Results: The response rate was 40%. If there was concordance between the radiological and histological findings, then there was a clear consensus on the appropriate B category. However, if there was discordance between the radiological and histological findings, then frequently there was poor agreement on the appropriate category. Analysis of these cases and supplementary questions on the criteria used to make a pathological categorisation showed that some pathologists are influenced by the radiological features or by the multidisciplinary discussion, rather than just using the histological features. Conclusions: This survey shows that pathologists frequently do not follow the National Health Service breast screening guideline that B categories should be based solely on the histological changes.